Achieving Organizational Success: How Organizational Citizenship Behavior Enhances Employee Performance? - Purwati, Dinar; Sah, Tomi (Journal of Applied Business Administration, 2024)
Achieving organizational success poses a primary challenge for leaders, wherein a focus on employee performance becomes pivotal in enhancing productivity and competitiveness. This study aims to explore the relationship between organizational citizenship behavior (OCB) and employee performance in the context of attaining organizational success. The research methodology employed is a quantitative approach with data collection conducted through questionnaires. In this research, the researcher utilizes simple linear regression analysis and t-tests to determine the extent of OCB's influence on employee performance. The findings indicate that OCB significantly and positively impacts employee performance, whereby each increase in OCB behavior by 1 point leads to a 0.516 increase in employee performance. However, the study's short duration and limited scope serve as constraints. Nevertheless, this research contributes theoretically and practically to organizational management in managing factors influencing employee performance.